Comparison of Outcome in Patients with and without Abdominal Drainage in Complicated Appendicitis - Mehdi, Syeda Rawash; Liaquat, Anum (Indus Journal of Bioscience Research, 2025)
Background: Managing complicated appendicitis presents surgical challenges, particularly due to potential postoperative complications like wound infections and intra-abdominal abscesses. The necessity of routine abdominal drainage in such cases remains a subject of debate. Objective: This study aimed to assess postoperative outcomes specifically wound infection, intra-abdominal abscess, and length of hospital stay in pediatric patients with complicated appendicitis, comparing those managed with abdominal drainage to those without. Material and Methods: A randomized controlled trial was carried out in the Pediatric Surgery Department of Nishtar Hospital, Multan, from May 31, 2024, to November 30, 2024. Sixty children aged 2 to 12 years with intra-operative findings of complicated appendicitis were included and randomly allocated into two groups: Group A (drain placement) and Group B (no drain). The primary outcomes measured were wound infection, intra-abdominal abscess formation, and hospital stay duration. Further analysis was stratified by age, gender, and symptom duration. Results: Postoperative wound infections were observed in 36.7% of patients in the drain group versus 20.0% in the non-drain group (p = 0.152). Abscess formation occurred in 16.7% and 23.3% of the drain and no drain groups, respectively (p = 0.519). The mean hospital stay was significantly longer in the drain group (5.77 ± 1.39 days) compared to the no drain group (4.64 ± 1.07 days, p = 0.001). Subgroup analysis revealed that prolonged hospital stays were more pronounced in younger children, males, and those with longer symptom duration. Conclusion: Using abdominal drains in complicated appendicitis may lead to extended hospital stays without significantly lowering postoperative complications. A selective approach to drainage may be more beneficial than routine use.